Gambaran Penggunaan Terapi Komplementer pada Pasien Diabetes Melitus Tipe II Di Puskesmas I Busungbiu Singaraja - Oktastyasa Putra, Wayan; Arwidiana, Dewa Putu; Suniyadewi, Ni Wayan (Pustaka Galeri Mandiri, 2025)
Diabetes mellitus is a chronic disease that requires long-term management. In addition to medical therapy, many patients utilize complementary therapy as a companion therapy to help reduce complaints, improve comfort, and quality of life. The use of complementary therapy is influenced by various characteristics of the patient, such as age, gender, and length of suffering from diabetes mellitus. Objective: This study aims to determine the description of the use of complementary therapy based on age, sex, and length of suffering from diabetes mellitus in patients with diabetes mellitus. This study used a quantitative descriptive design. The research sample amounted to 68 respondents of diabetes mellitus patients who were selected by total sampling technique. Data was collected using questionnaires and analyzed descriptively through cross-tabulation. The results showed that most of the respondents were >65 years old as 30 respondents (44.1%). The use of categorical complementary therapy was often found in 38 respondents (55.9%). Based on gender, female respondents amounted to 36 people (52.9%) and 32 man (47.1%), with the use of complementary therapy being relatively balanced. Based on the length of suffering from diabetes mellitus, respondents with a duration of >2 years were the largest group, namely 42 respondents (61.8%), with 21 respondents (30.9%) often using complementary therapy. The use of complementary therapies is more prevalent in elderly patients and with longer periods of diabetes mellitus. Complementary therapy is used as an adjunct therapy in the management of diabetes mellitus. Therefore, the role of health workers is needed in providing education related to the use of complementary therapy that is safe and in accordance with medical therapy